Determining the source data to form a control algorithm for hydrogen generators - Abramov, Yuriy; Basmanov, Oleksii; Krivtsova, Valentina; Mikhayluk, Andrey; Mikhayluk, Oleksandra (Eastern-European Journal of Enterprise Technologies, 2019)
Constructing an algorithm to control the technical condition of hydrogen generators employs using their amplitude-frequency and phase-frequency characteristics as the source data. Applying the classic method for defining such characteristics predetermines several drawbacks. One of the significant disadvantages is the long time required to form an array of source data. To shorten this time, determining the frequency characteristics of a hydrogen generator is carried out based on the results of measuring its transition function over discrete moments of time. During these time moments, the transition function is approximated by the Heaviside functions. Such an approach reduces the time for determining the frequency characteristics of a hydrogen generator by 1–2 orders. Applying the Kotelnikov–Nyquist–Shannon theorem for determining these discrete time moments is due to uncertainty about the maximum frequency of the test-signal spectrum. To avoid this uncertainty, discrete time moments for measuring the transitional function of a hydrogen generator are chosen under condition for the permissible error of its approximation. The error of approximation is determined based on the result from solving a test-problem that uses model characteristics as a standard for the frequency characteristics. It has been shown that at a sampling interval of (0.25¸2.5) ms the magnitude of such an error does not exceed 1.7 %. Inertial properties of the device that forms a test-impact have been taken into consideration. It has been shown that it is appropriate to apply such a procedure if the equivalent time constant of such a device exceeds the magnitudes of time constants for a hydrogen generator. The inertial properties are taken into consideration by introducing an additional multiplier, which contains the equivalent time constant of the device, to the analytical expressions for the frequency characteristics of a hydrogen generator